P084 An unusual case of Intradermal "Kissing" Naevus presenting as penile warts. (30th June 2016) - Goorney, Benjamin; Fitzgerald, David; Newsham, John
Abstract : Background/introduction: We describe a case of a 38 yr old white heterosexual male with Crohns disease presenting with warty lesions of the penis which were found on histological diagnosis to be benign intradermal naevi. The differential diagnosis included papular warts, skin tags, and in this case Crohns and pyoderma gangrenosum. Aim(s)/objectives: Initially presented with two smooth papular warty type lesions on the prepuce and glans adjacent to the coronal sulcus, which had been present for several months causing discomfort during sexual activity and unsightly appearance. Currently taking oral prednisolone and mesalazine for longstanding Crohns disease, with no other cutaneous manifestations, and had regular female partner. Results: Initially treated with Liquid Nitrogen application but with minimal resolution and in light of his medical history to exclude "metastatic" Crohns and associated pyoderma gangrenosum a punch biopsy was carried out. Histological appearances were that of a benign intradermal naevus with characteristic nests of naevus cells within the dermis only, there was no atypia present. He was subsequently referred to the urologist for surgical excision of the lesions. Discussion/Conclusion: Benign intradermal naevi or "kissing naevi" of Penis such as this are extremely rare there being only a handful previously reported. Due to the dermal location of naevus cells they usually present as skin coloured or slightly pigmented papules and may be confused with warts, skin tags or dermatofibroma. Treatment with surgical excision or laser therapy results in satisfactory functional and aesthetic outcomes.